If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 19 = 3x + 2 Reorder the terms: 19 + 2x = 3x + 2 Reorder the terms: 19 + 2x = 2 + 3x Solving 19 + 2x = 2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 19 + 2x + -3x = 2 + 3x + -3x Combine like terms: 2x + -3x = -1x 19 + -1x = 2 + 3x + -3x Combine like terms: 3x + -3x = 0 19 + -1x = 2 + 0 19 + -1x = 2 Add '-19' to each side of the equation. 19 + -19 + -1x = 2 + -19 Combine like terms: 19 + -19 = 0 0 + -1x = 2 + -19 -1x = 2 + -19 Combine like terms: 2 + -19 = -17 -1x = -17 Divide each side by '-1'. x = 17 Simplifying x = 17
| 3x-10=-2x+28 | | -12t+20+8t=5t-9 | | (5+x)(4+x)(x+3)=420 | | 27=7+37t-16t^2 | | ((5+x)(4+x)(x+3))-420=0 | | (7-i)-(8+3i)= | | 24x+30=24x+30 | | 2x-8y=-10 | | 5y-2x=-30 | | -33+58=98g-73 | | 10x-4=8x+14 | | 5x+6=55 | | 54=2x-18 | | 5x-2s+9=24 | | y-9=24 | | (3h-4)(3h-7)= | | 4(-2)+8(-2)+3(-2)+6= | | -30+6x=3x+33 | | 2x+(x-4)=2(x-3) | | p=0.1(475)+1 | | (9x+4)-(2x-8)=0 | | 10y+18=-3(5y-7)-8 | | 10x-4y+20=0 | | 15-k=20 | | 9a+6a^2=0 | | 3m(m+3)=420 | | 67.1=29.7-0.2w | | 16.1=0.1d+1 | | (3x-7)(4x-4)= | | 5+ln(x-1)=8 | | 10x=14+3x | | .42w-11=-.57w |